Sistema de gestión de la calidad para el proceso de investigación: Universidad de Otavalo, Ecuador - Becerra Lois, Francisco Ángel; Andrade Orbe, Adrián Manuel; Díaz Gispert, Lidia Inés (Universidad de Costa Rica, 2019)
The way in that the universities have adopted a focus centered in the administration of the quality to improve efficiency and effectiveness in the management of university processes and ensure their continuous improvement, is one of the main problems of the modern university management. The general objective of this paper is to propose a Quality Management System (QMS) for the research process, based on the ISO 9001: 2015 standard and the institutional evaluation model used in Ecuador to certify the quality of the universities. The University of Otavalo included in its strategic plan 2015-2020 the design and implementation of a QMS, which required the development of an exploratory and descriptive research, and the use of a mixed methodology, structured in seven stages, that covered the definition of the type of study up to the design of the QMS, and included structured and unstructured research instruments, prepared for the collection of information. The final result of the work was an informed diagnosis of the situation of the research process in the institution and the design and implementation of a QMS, which is composed of five subprocesses with their respective characterizations, flowcharts and procedures, including the documents and records required to assure its quality. Its application has allowed to improve the organization of the investigative process, evidenced in the results in the management of projects and in the achieved scientific production.